1995
DOI: 10.1002/pd.1970150202
|View full text |Cite
|
Sign up to set email alerts
|

An audit of trisomy 16 in man

Abstract: Sufficient information is now available from the literature to produce an audit of trisomy 16, in a theoretical cohort of 100,000 recognized pregnancies, from gametogenesis to term and onwards. Recent reports of premature separation of chromosome 16 bivalents during maternal meiosis I provide a novel mechanism for generation of this aneuploidy. Most, if not all, errors resulting in recognized mosaic and non-mosaic trisomy 16 pregnancies investigated using polymorphic DNA markers appear to originate at that sta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
79
1

Year Published

1996
1996
2006
2006

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 91 publications
(83 citation statements)
references
References 50 publications
3
79
1
Order By: Relevance
“…The distribution of the trisomies in the CPMs in our data fits the pattern found by Wolstenholme [1995; in his reviews of case series of CPM for trisomies 2, 3, 7, 8, 9, 16, and 22 from the literature, except for trisomy 8: A consistent pattern with trisomy 2 mainly as mosaic CPM type II; trisomy 3 as mosaic CPM type I; trisomy 7 and 9 as either mosaic CPM type I or II, with a few instances of non-mosaic CPM type I and/or CPM type III, and trisomy 16 as non-mosaic CPM type III or I. Our figures for trisomy 22 CPM are too small for comparison, but for trisomy 8 our data showed mosaic CPM type I to be as likely as mosaic CPM type II, while Wolstenholme found trisomy 8 mainly as mosaic CPM type II.…”
Section: Discussionsupporting
confidence: 80%
“…The distribution of the trisomies in the CPMs in our data fits the pattern found by Wolstenholme [1995; in his reviews of case series of CPM for trisomies 2, 3, 7, 8, 9, 16, and 22 from the literature, except for trisomy 8: A consistent pattern with trisomy 2 mainly as mosaic CPM type II; trisomy 3 as mosaic CPM type I; trisomy 7 and 9 as either mosaic CPM type I or II, with a few instances of non-mosaic CPM type I and/or CPM type III, and trisomy 16 as non-mosaic CPM type III or I. Our figures for trisomy 22 CPM are too small for comparison, but for trisomy 8 our data showed mosaic CPM type I to be as likely as mosaic CPM type II, while Wolstenholme found trisomy 8 mainly as mosaic CPM type II.…”
Section: Discussionsupporting
confidence: 80%
“…23,27,28 Unlike Hahnemann and Vejerslev, 23 we found one case of nonmosaic trisomy 22 in both placental tissues associated with a normal male karyotype in amniocytes. The CPMs due to structural rearrangements were equally distributed between types I and II.…”
Section: Confined Placental Mosaicisms and Upd Risk Assessmentcontrasting
confidence: 60%
“…Most of these newborns do not exhibit congenital anomalies apart from severe intrauter ine growth retardation, and not all catch up later. In addi tion, a proportion of gestations with 16-trisomic placentas with or without fetal UPD terminate through fetal demise [4], Only in a minority of newborns with maternal UPD 16 are congenital anomalies present, most often anal atre sia [2,6] and cardiac defects [7,8], followed by inguinal hernia [9] and, in single patients, hypospadias [7], disloca tion of elbows [7], hypothyroidism [9], clubfeet [7] and lung hypoplasia [6], The patient with most congenital anomalies [7] was the only one with complete isodisomy. Thus, his congenital malformations could also be due to the homozygous state of a mutated recessive gene and not predominantly, as possibly in the other patients who showed segmental hetero-and segmental isodisomy, to imprinting or hidden mosaicism.…”
Section: Discussionmentioning
confidence: 99%
“…Further findings in a proporUniparental disomy (UPD), maternal and/or paternal, has so far been reported for about half of the chromo somes [1] and has, due to imprinting, an impact on the phenotype for chromosomes 6 (paternal), 7 (maternal), 14 (probably maternal and paternal), 15 (maternal and pater nal), 16 (possibly maternal) and lip 15 (paternal). For tion of patients with maternal UPD 16 include prenatal demise, anal atresia, inguinal hernias, microcephaly of prenatal onset and others [3,4], However, fetuses with UPD 16 and completely normal phenotype have also been observed, and it has therefore been suggested that the phe notype in the cases with congenital developmental defects is due to hidden mosaicism for trisomy 16 rather than to UPD [5],…”
mentioning
confidence: 99%